Antibody diversity in IVIG: Therapeutic opportunities for novel immunotherapeutic drugs - von Gunten, Stephan; Schneider, Christoph; Imamovic, Lejla; Gorochov, Guy (Frontiers in Immunology, 2023)
Significant progress has been made in the elucidation of human antibody repertoires. Furthermore, non-canonical functions of antibodies have been identified that reach beyond classical functions linked to protection from pathogens. Polyclonal immunoglobulin preparations such as IVIG and SCIG represent the IgG repertoire of the donor population and will likely remain the cornerstone of antibody replacement therapy in immunodeficiencies. However, novel evidence suggests that pooled IgA might promote orthobiotic microbial colonization in gut dysbiosis linked to mucosal IgA immunodeficiency. Plasma-derived polyclonal IgG and IgA exhibit immunoregulatory effects by a diversity of different mechanisms, which have inspired the development of novel drugs. Here we highlight recent insights into IgG and IgA repertoires and discuss potential implications for polyclonal immunoglobulin therapy and inspired drugs.